The Effect Of Total Asset Turnover, Debt To Equity Ratio, And Current Ratio On Return On Equity In The Plastic And Packaging Sub-Sector Listed On The Stock Exchange Indonesia Effects Period 2019-2022 - Raysa Alifia; Austin Alexander Parhusip (LPPM STIE Kasih Bangsa, 2024)
This study was conducted to understand how Total Asset Turnover (TATO), Debt to Equity Ratio, and Current Ratio affect the overall Return On Equity (ROE) in plastic and packaging companies listed on the Indonesia Stock Exchange between 2019 and 2022. This study uses a quantitative method by the author. The data used in this study consists of the annual financial reports of the Plastic and Packaging sub-sector listed on the Indonesia Stock Exchange during the period 2019 to 2022. There are 8 companies used as samples in this study. Based on data from the research table, the Total Asset Turnover (X1) variable is proven to have a partial and significant effect on the Return On Equity of the plastic and packaging sub-sector listed on the IDX. Data from the research table shows that the Debt to Equity Ratio variable has a negative but insignificant effect on the Return On Equity of plastic and packaging sub-sector companies listed on the IDX. Based on data from the research table, it can be seen that the Current Ratio variable partially does not have a significant effect on the Return On Equity in the plastic and packaging sub-sector on the IDX. The conclusion of this discussion shows that Total Asset Turnover (X1), Debt to Equity Ratio (X2), and Current Ratio (X3), all have a significant and simultaneous influence on Return On Equity in the Plastics and Packaging sub-sector listed on the Indonesia Stock Exchange from 2019 to 2022.